Pharmacokinetics of Piperacillin-Tazobactam in Anuric Intensive Care Patients during Continuous Venovenous Hemodialysis - Mueller, Silke C. (American Society for Microbiology, 2002)
The pharmacokinetics of piperacillin-tazobactam were investigated in eight anuric intensive care patients treated by continuous venovenous hemodialysis (CVVHD). The elimination half-life of piperacillin was 4.3 ± 1.2 h, and that of tazobactam was 5.6 ± 1.3 h. The contribution of CVVHD to the overall elimination was relevant (>25%) for both drugs.